Penguins Search Optimization Algorithm (PeSOA) for chaotic synchronization system - Maamri, Fouzia; Bououden, Sofiane; Djellab, Hanane; Boulkaibet, Ilyes (University of Eloued جامعة الوادي, 2022)
Information encryption is a security process where data is encoded using chaotic signal. stabilization and synchronization in chaotic systems for secure information can be achieved using the metaheuristic algorithms. In this work Penguins Search Optimization Algorithm (PeSOA) which is inspired by penguin’s social behavior is applied to synchronize chaotic encryption signal. PeSOA algorithm explores space with random and iterative search in order to find symmetric encryption key of the chaotic system in both transmission and reception. Identification based on metaheristic optimization Algorithm (PeSOA) is used to improve the accuracy of initial conditions and control parameters of Chua’s chaotic generator by minimizing errors between the estimated and identified value. Simulation results show the effectiveness of the PeSOA algorithm to generating symmetric key of encryption process and synchronizing both chaotic circuit of transmitter and receiver one.
Forum Intervention of Artificial Intelligence and Its Applications. Faculty of Exat science. University of Eloued
Keywords: Metaheuristic, PeSOA, Chaos, Encryption, Synchronization, Optimization.